Electronic metal–support interactions enhance the ammonia synthesis activity over ruthenium supported on Zr-modified CeO2 catalysts. Issue 56 (25th May 2016) - Ma, Zhanwei; Xiong, Xumao; Song, Chengli; Hu, Bin; Zhang, Weiqiang
Abstract : Doping Zr 4+ alters the electronic properties of the support. The electronic metal–support interaction produces the upshift of d-band center of Ru nanoparticles, which further influences the catalytic activity of ammonia synthesis. Abstract : Here we report that the electronic metal–support interaction influences the catalytic activity of ammonia synthesis. This effect produces an upwards shift of the d-band center of Ru nanoparticles. The upward shift of the d-band center of the Ru nanoparticles is considered to enhance the dissociation of the N2 molecule.